Health state utilities and quality of life in patients with hepatitis B - Woo, Gloria (Pulsus Group Inc, 2012)
BACKGROUND: The effect of chronic hepatitis B (CHB) infection on health-related quality of life (HRQoL) and health state utilities has not been well characterized. OBJECTIVE: To measure utility scores and HRQoL across disease states associated with CHB infection. METHODS: Patients attending four tertiary care clinics for CHB were approached between July 2007 and March 2009. Respondents completed version 2 of the Short-Form 36 Health Survey, the EQ5D, a visual analogue scale, the Health Utilities Index Mark 3, standard gamble, and demographics and risk factor surveys in English, Cantonese or Mandarin. Charts were reviewed to determine disease stage and comorbidities. RESULTS: A total of 433 patients were studied: 294 had no cirrhosis; 79 had compensated cirrhosis; seven had decompensated cirrhosis; 23 had hepatocellular carcinoma; and 30 had received a liver transplant. The mean standard gamble utilities for these disease states were 0.89, 0.87, 0.82, 0.84 and 0.86, respectively. HRQoL scores in noncirrhotic patients were similar to those of the general population. Scores of patients with compensated cirrhosis were not significantly lower; however, patients with decompensated cirrhosis and hepatocellular carcinoma had significantly lower HRQoL scores compared with noncirrhotic patients (P<0.05). Similar scores were observed among patients on and off oral antiviral treatment. Post-liver transplant patients had a higher HRQoL than patients with decompensated cirrhosis. Age, number of comorbidities and relationship status were significantly associated with HRQoL scores. CONCLUSIONS: HRQoL in CHB patients is only impaired in the later stages of liver disease. Neither CHB infection nor antiviral treatment is associated with a lower quality of life.